Penerapan Metode Analytical Hierarchy Process (AHP) Dalam Pemilihan Smartphone - Satria Wiguna, I Made Eko; Widiartha, I Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p02, 2022)
Smartphone has become a part of our daily live nowadays. Today, smartphones brand is competitive each other with their innovation on smartphone. There are much different prices from cheaper to expensive. There are also have different specifications with different purposes. This can be confusing if we want to buy a smartphone. They created a product with different specifications and price. Analytical Hierarchy Process (AHP) can solve this problem by using to make recommendations or decision. AHP is a part of decision support system methods (SPK). AHP using weight to make calculation in decision prosses making. This make AHP method result logically and realistic. AHP method breakdown the problem by making hierarchy, therefore the problem become structured and systematized. This paper, using five aspects as criteria. There are RAM, camera features, screen size, battery, and price. This are commonly used to considering before choosing a smartphone. This paper will use AHP method to make recommendations for smartphone based on priority of criteria. Keywords : AHP, Decision Support System, Decision, Recommendation, Hierarchy